2010
DOI: 10.3109/09638288.2010.482174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a rehabilitation programme on daily functioning, participation, health-related quality of life, anxiety and depression in liver transplant recipients

Abstract: Rehabilitation using supervised exercise training and daily physical activity counselling can positively influence daily functioning, participation and HRQoL among fatigued liver transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 30 publications
(37 reference statements)
1
35
0
6
Order By: Relevance
“…In this study, physical adaptation of LTRs was improved positively after the support group intervention. In the literature, similarly to our study, it has been reported that mindfulness meditation group interventions were positively affected sleep 13,14 and the physical health of organ transplant recipients; 14 that physical rehabilitation positively affected physical health; 16 that exercise and diet affected physical function and exercise capacity; 17 and that fitness rehabilitation affected physical health and physical behavior. 15 In a study on the effectiveness of an exercise and diet program, patients attending the program had a better exercise capacity in the short term (in the fourth month) than did control patients; however, the positive effect of the program did not continue in the long term (in the tenth month).…”
Section: Effects Of Support Group Intervention In Physical Adaptationsupporting
confidence: 65%
See 3 more Smart Citations
“…In this study, physical adaptation of LTRs was improved positively after the support group intervention. In the literature, similarly to our study, it has been reported that mindfulness meditation group interventions were positively affected sleep 13,14 and the physical health of organ transplant recipients; 14 that physical rehabilitation positively affected physical health; 16 that exercise and diet affected physical function and exercise capacity; 17 and that fitness rehabilitation affected physical health and physical behavior. 15 In a study on the effectiveness of an exercise and diet program, patients attending the program had a better exercise capacity in the short term (in the fourth month) than did control patients; however, the positive effect of the program did not continue in the long term (in the tenth month).…”
Section: Effects Of Support Group Intervention In Physical Adaptationsupporting
confidence: 65%
“…32 In addition, Keidar and associates (2001a) 18 reported that support group interventions had a positive influence on relationships between the family members of liver, kidney, and pancreas transplant patients. Van Ginneken and associates (2011) 16 showed that exercise and diet improved patients' autonomy, roles in their families, and social relationships.…”
Section: Effects Of the Support Group Intervention On Psychological Amentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, many patients have to wait on liver transplantation waiting lists, and the number of patients awaiting transplants is greater than the ones receiving (15). Therefore, a relevant alternative to these patients might be to begin physical training and multidisciplinary rehabilitation programs (16,17). Physical exercise may reduce cardiovascular and neuromuscular variable impairments, improving both life quality and expectancy of these patients (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%